Trends in enrollment, retention, and graduation of United States veterinary technicians/nurses schools - Kogan, Lori R.; Jensen, Wayne A. (Frontiers in Veterinary Science, 2024)
Objective: There is a significant shortage of veterinary technicians. To help address this issue, there has been a call to increase the capacity of US VT/N educational programs. Yet, the current challenges within the field may be negatively impacting the number of people deciding to pursue VT/N certification. To assess this possibility, this study was designed to explore the enrollment, retention, and graduation trends within US VT/N educational programs.Explore the trends between 2018 -2022 in enrollment, retention, and graduation of veterinary technicians/nurses (VT/N) at educational programs located in the United States.Sample: Educators and administrators working in US VT/N educational programs.Procedures: An electronic survey distributed via an anonymous link within emails sent from the Association of Veterinary Technician Educators. Results: A total of 82 responses from educators and administrators working in US VT/N educational programs were received. Forty-three percent of participants indicated a decrease in student enrollment in the last five years. The factors seen to have the largest significant impact were "More potential students not convinced being credentialed will lead to a difference in job duties when compared to non-credentialed work", "More potential students who don't think being credentialed will lead to a substantial increase in pay when compared to non-credentialed work" and "More potential students not willing/able to invest the time needed to become credentialed". A total of 60% reported an increase in retention efforts within the last five years. The services most commonly reported as increasing included mental health support and academic mentoring.Conclusions and Clinical Relevance: This study suggests that an increased number of potential VT/N students are deciding that being credentialed is not worth the time or money. While additional resources directed towards recruitment and retention are needed within VT/N educational programs, without systematic changes within the field, it is likely that there will be a continued decline in the number of interested applicants.